The influence of anime as Japanese popular culture among art and design students - Yusof, Nor Afian; Mastor, Khairul Anwar; Mamat, Maharam; Keng, Lim Kar; Haron, Hamdzun; Tahir, Hanafi Mohd; Jaafar, Rafuzan; Baharum, Khairudin (Nurture, 2023)
Purpose: The objective of this study is to investigate the influence of anime on the prevalence of Japanese popular culture among Art and Design students. Design/Methodology/Approach: This study employed a questionnaire-based quantitative survey of 186 college students enrolled in arts and design programmes at three higher education institutions. Five Likert-scale questionnaires were utilised to collect the data, which was subsequently analysed using SPSS (Statistical Package for the Social Sciences). Findings: The majority of respondents had rather limited time to watch anime. This is due to the time constraints for completing their tasks and projects. That was proven by the low average viewing rate of anime among respondents. The findings showed only 39 respondents watched anime for more than 6 hours and above, while the majority of 147 others, or 79%, watched anime for 5 hours and below in a week. Nevertheless, the influence of Japanese popular culture still has a significant impact on this study, even at low and moderate levels. Conclusion: This study found that anime has managed to spread the influence of Japanese popular culture among respondents despite being weak and moderate. This result was also due to the low frequency of watching anime. The data may be different if the average frequency of watching anime is high. Research Limitations: This study is limited to art and design students only. For future studies, it is recommended that studies be conducted on other majors to find the difference in results. Contribution to Literature: This study may add to the literature of relatively understudied anime-related studies, especially in Malaysia.